The Analysis of Semiotic Signs on Forest Fires’ Posters - Pratiwi, Desak Putu Eka; Vina Widiadnya, I Gusti Ayu; Emi Puspita Sari, Ni Luh (Humanis; Vol 25 No 2 (2021), 2021)
Forest fires are one of the global issues and need global concern. A campaign through forest fire posters on social media is a way to spread a message all over the world to prevent forest fires and save the earth from disaster. This study aims to discover the meaning of verbal and nonverbal signs used on forest fire posters. Verbal signs are about the text, either words or sentences while nonverbal signs are about pictures. The use of these two signs on a poster is meant to make people understand the message within it. The data were taken from three selected forest fire posters. The data were collected by observation method. The data were analyzed by a qualitative method using the theory of Semiotic by Barthes (1998) and supporting theory by Wierzbicka (1996). The finding shows that both verbal and nonverbal signs have important purposes such as giving some information about the impact of forest fires on nature and human life as well as warning people to be more responsible and aware of this global issue.